Expression of NADPH-d in the vagal nuclei of the chronic esophagitis model in rats - (:unkn) unknown (My University, 2014)
0

Aim: To evaluate the changes in the number of NADPH diaphorase (NADPH-d) stained neurons in the vagal nuclei in a chronic esophagitis model. Materials and methods: There were 3 groups of rats examined: 1) a chronic gastroesophageal reflux rat group, which was created by a partial gastric outlet obstruction; 2) a sham group; and 3) a ranitidine treated group. Serial sections of brainstems of all groups were cut and NADPH-d staining, which selectively stains the nitric acid synthase-containing neurons, was done. Results: Histopathological changes due to chronic reflux esophagitis was observed in the reflux group. The ranitidine treatment and sham control groups showed no changes related to esophagitis. The staining in the dorsal motor nucleus of the vagus and nucleus tractus solitarius showed statistically significant differences compared to the control group (P < 0.0001). Conclusion: The increased nitric oxide expressions in the dorsal vagal nucleus and nucleus tractus solitarius are most probably due to adaptive changes to disturbed esophageal motility and mucosal damage.
Keywords: Cerrahi